2019
DOI: 10.2134/cftm2019.05.0032
|View full text |Cite
|
Sign up to set email alerts
|

Corn Yield Response to Row Spacing and Plant Population in Iowa

Abstract: Corn (Zea mays L.) planted in narrow row spacing (<30-inch) with high plant population has become a recent interest in the US Corn Belt to increase grain yield. We evaluated the impact of row spacing and plant population on corn grain yield across 22 site-years in Iowa from 2009 to 2018. Experiments were designed as a split-plot with two row spacings, 20-and 30-inch, as the main-plot and three to four plant populations, ranging from 30,000 to 42,000 plants acre -Crop Forage Turfgrass Manage. 5:0032.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
(97 reference statements)
2
10
0
Order By: Relevance
“…A synthesis analysis of modern corn hybrids from 22 US states and two Canadian provinces from 2000 to 2014 found 84,000 seeds ha −1 , the point where corn yields are generally maximized (Assefa et al., 2016). Similar results were found across several hybrids in Iowa (Licht et al., 2019).…”
Section: Resultssupporting
confidence: 82%
“…A synthesis analysis of modern corn hybrids from 22 US states and two Canadian provinces from 2000 to 2014 found 84,000 seeds ha −1 , the point where corn yields are generally maximized (Assefa et al., 2016). Similar results were found across several hybrids in Iowa (Licht et al., 2019).…”
Section: Resultssupporting
confidence: 82%
“…When selecting equipment, row spacing influences sprayer wheel base, boom length, and harvest capability. Furthermore, row spacing in combination with plant populations influence interplant competition, crop performance, and final yield specifically in corn (Zea mays) grain production (Bruin and Pederson, 2008;Heitholt and Sassenrath, 2010;Licht et. al., 2019;Widdicombe and Thelen, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…When selecting equipment, row spacing influences sprayer wheel base, boom length, and harvest capability. Furthermore, row spacing in combination with plant populations influence interplant competition, crop performance, and final yield specifically in corn ( Zea mays L.) grain production (Bruin & Pederson, 2008; Heitholt & Sassenrath, 2010; Licht et al., 2019; Widdicombe & Thelen, 2002). Single‐row (SR) narrower than 30 inches have become the focal point for determining if an increase in interplant spacing improves overall crop performance in grain‐producing monocultures (Haegele et al., 2014; Thelen, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in the Midwest have reported a yield advantage when row spacing is decreased to less than 76 cm (Nielsen, 1988;Porter et al, 1997;Widdicombe & Thelen, 2002;Shapiro & Wortmann, 2006), while others have reported no yield differences (Farnham, 2001;Van Roekel & Coulter, 2012;Robles et al, 2012). Grain yield responses to narrower rows have been inconsistent but are often more consistently observed in high-yielding environments (Licht et al, 2019).…”
Section: Introductionmentioning
confidence: 99%